(- 4 + 2) - 3(2 - 7)
First: use the order of operations > PEMDAS >
( ), exponents, multiplication, division, addition and subtraction...
(-2) - 3(-5)
- 2 - (-15)
- 2 + 15
= 13
2007-01-26 05:50:50
·
answer #1
·
answered by ♪♥Annie♥♪ 6
·
1⤊
1⤋
(-4 + 2) – 3(2 – 7) =
-2 -6 + 21 = -8 + 21 = 13
<>
2007-01-26 05:54:44
·
answer #2
·
answered by aeiou 7
·
1⤊
0⤋
-4+2-6+21=13
2007-01-26 05:48:58
·
answer #3
·
answered by excalibur_gordon 2
·
1⤊
0⤋
(-4 + 2) - 6+ 21
-10+23
= 13
2007-01-26 05:54:36
·
answer #4
·
answered by jessica 2
·
1⤊
0⤋
= (-4 + 2) - 3(2-7)
= -2 - 3(-5)
= -2 + 15
= 13
2007-01-26 05:51:35
·
answer #5
·
answered by 2
·
1⤊
0⤋
(-2) - 6 + 21 = -8 + 21 = 13
2007-01-26 05:59:53
·
answer #6
·
answered by Anonymous
·
1⤊
0⤋
(-4 + 2) – 3(2 – 7)
-4+2-6+21
-2-6+21
-8+21
13
2007-01-26 05:54:11
·
answer #7
·
answered by 7
·
1⤊
0⤋
-2-3(-5)=-2+15=13
2007-01-26 05:49:59
·
answer #8
·
answered by Jim L 2
·
1⤊
0⤋
(-4+2)-3(2-7)
first u add and subract the numbers inside the prenthases
(-2)-3(-5)
then u multiply 3 and 5
-2 +15
then u add the two last numbers
13
2007-01-26 05:55:11
·
answer #9
·
answered by lubna h 1
·
1⤊
0⤋
-4+2-6+21=your answer
2007-01-26 05:47:21
·
answer #10
·
answered by Professor Maddie 4
·
1⤊
0⤋